Perancangan Panti Sosial Anak dengan Pendekatan Arsitektur Perilaku pada Masa Pandemi Covid-19 - Priskila, Nadia; Anggraeni, Dhita Wahyu (Universitas muhammadiyah palembang, 2023)
Children are individuals who will experience growth and development. Every child has the potential and talent in him if he gets learning both in terms of knowledge and creativity. In the city of Palembang, there are many homeless children, beggar children and underprivileged street children. This makes the current state of the covid-19 pandemic even more dangerous for children, because they are afraid that many children will be exposed to the covid-19 virus. Therefore, the existence of a children's social institution building can help street children to get a decent life by providing a sense of comfort with a recreational atmosphere and various self-skill facilities to be able to provide a more secure future. The design of children’s social homes will go through design methods with behavioral architecture. The architecture approach of behavior is driven by how activity or behavior of any child is subsequently incorporated into the design of the building, so the design of a child’s orphanage building has the character of every room that matches that of the child’s behavior. This design will also apply a lifecycle theme related to the life cycle that continues to change in growth. The design of the children's social home is expected to be a forum in helping children to get a prosperous life, work and achieve.